The New Managerialism and Public Service Professions Change in Health, Social Services and Housing - Kirkpatrick, I. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2005)
The New Managerialism and Public Service Professionals is a fresh and insightful analysis of the changes that have taken place in the UK public sector over the past twenty years. Unlike many other recent accounts it is not assumed that these policy goals were always implemented or that new approaches to the management of services are necessarily effective. Drawing on an extensive review of major published research it considers developments in three areas: the National Health Service, social services and housing. This analysis reveals marked differences in the way the professions responded to change and draws attention to some significant costs associated with restructuring.